Verso il monitoraggio ambientale dell’Antartide su scala globale. Il progetto VECTRA - CAPRA, Alessandro; MANCINI, Francesco; Coren, F; Frezzotti, M; Sterzai, P; Vidmar, R. (ASITA, 1999)
Verso il monitoraggio ambientale dell’Antartide su scala globale. Il progetto VECTRA.